Ambiguous act equilibria - Sophie Bade (Max Planck Institute for Research on Collective Goods, 2010)
A game-theoretic framework that allows for explicitly randomized strategies is used to study the e ect of ambiguity aversion on equilibrium outcomes. The notions of 'independent strategies' as well as of 'common priors' are amended to render them applicable to games in which players lack probabilistic sophistication. Within this framework the equilibrium predictions of two player games with ambiguity averse and with ambiguity neutral players are observationally equivalent. This equivalence result does not extend to the case of games with more than two players. A translation of the concept of equilibrium in beliefs to the context of ambiguity aversion yields substantially di erent predictions even for the case with just two players.
Keywords: C72; D81; 330; Uncertainty Aversion; Nash Equilibrium; Ambiguity; Entscheidung bei Unsicherheit; Risikoaversion; Spieltheorie; Nash-Gleichgewicht; Theorie